Eight days a week [videorecording (DVD)] : the touring years - McCartney, Paul; Starr, Ringo; Lennon, John, 1940-1980; Harrison, George, 1943-2001 (UMe, 2016)
Based on the first part of The Beatles' career the period in which they toured and captured the worlds acclaim. Explores how John Lennon, Paul McCartney, George Harrison and Ringo Starr came together to become this extraordinary phenomenon. It explores their inner workings how they made decisions, created their music and built their collective career together all the while, exploring The Beatles' extraordinary and unique musical gifts and their remarkable, complementary personalities.